Movement patterns of tourists. (December 2019) - Zhong, Lina; Sun, Sunny; Law, Rob
Abstract: Previous studies have explored the movement patterns of tourists via interviews or observations. However, these studies failed to provide an overall picture that can facilitate the effectiveness of destination marketing. Given that Tibet has become more accessible at present and the important role of attractions in a destination, the present study calculates the probabilities of tourists' movement routes in different prefectures in Tibet through mobile phone signals. Specifically, the present study introduces a methodological approach by using Tibet as an example to identify the movement patterns of tourists from one attraction to another to examine the attractiveness of attractions/prefectures based on the extended contemporary urban transportation model. Findings indicate that tourists can visit remote attractions only if the destination has an absolute advantage/attractiveness. These findings can assist destination managers in exploring possible ways to enhance the attractiveness of a destination's attractions. Highlights: The present study introduces a methodological approach based on the extended contemporary urban transportation model. The present study calculates the probabilities of tourists' movement routes in different prefectures in Tibet. Findings can assist destination managers in exploring possible ways to improve the attractiveness of a destination.